2019
DOI: 10.1186/s12914-019-0206-6
|View full text |Cite
|
Sign up to set email alerts
|

A model explaining refugee experiences of the Australian healthcare system: a systematic review of refugee perceptions

Abstract: Background: Refugees have significant unmet health needs. Delivering services to refugees continues to be problematic in the Australian healthcare system. A systematic review and thematic synthesis of the literature exploring refugee perceptions of the Australian healthcare system was performed. Methods: Titles and abstracts of 1610 articles published between 2006 and 2019 were screened, and 147 articles were read in full text. Depending on the type of study, articles were appraised using the Modified Critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 63 publications
7
74
0
Order By: Relevance
“…A strength of synthesis of qualitative data, is that themes may be more transferable to other contexts and have greater potential to inform policy and practice, in comparison to individual qualitative studies [6,40]. Our findings may also be transferable to other healthcare settings, as indicated by other systematic reviews which explored experiences of this population in the host countries [4,17]. In addition, the methodology used provides a transparent link between the primary studies and the conclusions drawn in this review.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 82%
See 1 more Smart Citation
“…A strength of synthesis of qualitative data, is that themes may be more transferable to other contexts and have greater potential to inform policy and practice, in comparison to individual qualitative studies [6,40]. Our findings may also be transferable to other healthcare settings, as indicated by other systematic reviews which explored experiences of this population in the host countries [4,17]. In addition, the methodology used provides a transparent link between the primary studies and the conclusions drawn in this review.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 82%
“…The majority of the global refugee population are hosted in poorly resourced countries. However, inequalities in health outcomes and healthcare among this group across a number of services also exist in high-income countries [4][5][6]. This raises the importance of addressing this group's health needs in highly-developed countries.…”
mentioning
confidence: 99%
“…Research investigating the broad resettlement experiences for people from refugee backgrounds in high income countries has proliferated in recent years [54], however less research has focused on the experiences of refugees in regional or rural areas, particularly regarding health in those environments [55], and there is very limited research outside Australia on the experiences of refugees in regional or rural areas. The research that has been conducted has indicated that successful settlement is dependent on a number of factors [11,47,56,57] such as attitudes of the host community [41]; rural employment opportunities [58]; and size and connections of the incoming community [59], and highlights the importance of local contexts for refugee resettlement [15,60].…”
Section: Regional Resettlement In Australiamentioning
confidence: 99%
“…Building both clinical and administrative capacity is essential and underpins sustainable practice utilising the available MBS rebate. It has been established that the initial 6 months' post arrival can be challenging (Au et al 2019) and the additional time the MIRHS nurse is able to provide support in terms of both health system navigation (access) and health literacy (management) is critical to positive patient outcomes in a time-poor general practice context.…”
Section: Resultsmentioning
confidence: 99%